Efficient Detection and Size Determination of Crystal Originated “Particles” (COPs) on Silicon Wafer Surface Using Optical Scattering Technique Integrated to an Atomic Force Microscope - Lee, W.-P.; Yow, H.-K.; Tou, T.-Y. (2004)
Dark-field optical scattering technique is adopted in a surface defect detection system (DDS) to allow an efficient and cost-effective detection and size determination of the crystal originated "particles" (COPs) on polished silicon wafer surface before atomic force microscope (AFM) measurement. The effects of laser beam power, beam angle, beam profile, wafer rotation and intensified CCD (ICCD) camera exposure time on the scattered light diameter of preselected COPs were investigated. An AFM was integrated to the DDS through coordinate linkage to confirm the diagonal length, shape and type of the CON detected. A correlation curve between the scattered light diameters and the actual diagonal lengths of the COPs was then obtained. Once the correlation is established, the size of COP on any wafer surface can be estimated simply by referring to the correlation curve without constant reference to the AFM. In this study, the detection of a single-type COP with a diagonal length of 60 nm was demonstrated.